2016
DOI: 10.1111/ajad.12344
|View full text |Cite
|
Sign up to set email alerts
|

Cue-induced craving to paraphernalia and drug images in opioid dependence

Abstract: Background and Objectives Stimuli that are repeatedly paired with substance use, such as drug paraphernalia, can themselves elicit drug craving. The aim of this study was to examine whether particular cue types elicit greater craving responses than others among individuals with opioid dependence. Methods Participants seeking inpatient treatment for opioid dependence were recruited for a study of cue-induced craving. This sample (N=50), included 25 primary heroin users, 20 primary prescription opioid users, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…We found that oral drug cues reliably reinstated extinguished drug-seeking behavior in both male and female mice. These data support the observation that both oral and intravenous-associated drug cues are capable of causing cravings in human users (McHugh, Fulciniti, Mashhoon et al, 2016). In addition, these data indicate that drugs associated with oral ingestion, despite having less immediate effects than intravenous use (Gasior, Bond & Malamut, 2016;Kirsh, Peppin & Coleman, 2012;Leow, Smith, Watt et al, 1992), are nonetheless capable of invigorating drug-seeking behavior.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that oral drug cues reliably reinstated extinguished drug-seeking behavior in both male and female mice. These data support the observation that both oral and intravenous-associated drug cues are capable of causing cravings in human users (McHugh, Fulciniti, Mashhoon et al, 2016). In addition, these data indicate that drugs associated with oral ingestion, despite having less immediate effects than intravenous use (Gasior, Bond & Malamut, 2016;Kirsh, Peppin & Coleman, 2012;Leow, Smith, Watt et al, 1992), are nonetheless capable of invigorating drug-seeking behavior.…”
Section: Discussionsupporting
confidence: 82%
“…Environmental stimuli such as drug-associated cues influence relapse in opioid addicted individuals (Hyman, Fox, Hong et al, 2007;O'Brien, Childress, McLellan et al, 1990). In the clinic, intravenous users selfreport significantly higher ratings of craving than oral users in response to drug-associated cues (McHugh, Fulciniti, Mashhoon et al, 2016;McHugh, Park & Weiss, 2014). These data predict that oral prescription opioid users are less susceptible to relapse triggered by drug-associated cues than intravenous users.…”
Section: Introductionmentioning
confidence: 93%
“…These data support the observation that both oral and intravenous-associated drug cues are capable of causing cravings in human users. 20 In addition, these data indicate that drugs associated with oral ingestion, despite having less immediate effects than intravenous use, 6,7,10 are nonetheless capable of invigorating drug-seeking. Further research will be necessary to evaluate the roles of other reinstating stimuli (stress, drug-prime), extinction (punished, non-drug choice), and potential for incubation effects in the oral route.…”
Section: Resultsmentioning
confidence: 99%
“…Even among heroin users who have been abstinent for greater than a year, drug-related cues still have the potential to elicit craving responses (47, 48), highlighting the enduring nature of craving among patients with a history of drug dependence. The influence of different cues on craving may also be dependent on the type of opioid dependence: in heroin dependence, cue-related craving was stimulated more intensely by paraphernalia images (e.g., needles), whereas patients with analgesic dependence were more stimulated by pills and pill bottles (46). The relationship between life stressors, craving, and relapse is complex and likely to be subject to significant inter-individual differences.…”
Section: Craving In Clinical Practicementioning
confidence: 99%